Common Molecular Subtypes Among Asian Hepatocellular Carcinoma and Cholangiocarcinoma - Jittiporn Chaisaingmongkol (2018)
© 2017 Intrahepatic cholangiocarcinoma (ICC) and hepatocellular carcinoma (HCC) are clinically disparate primary liver cancers with etiological and biological heterogeneity. We identified common molecular subtypes linked to similar prognosis among 199 Thai ICC and HCC patients through systems integration of genomics, transcriptomics, and metabolomics. While ICC and HCC share recurrently mutated genes, including TP53, ARID1A, and ARID2, mitotic checkpoint anomalies distinguish the C1 subtype with key drivers PLK1 and ECT2, whereas the C2 subtype is linked to obesity, T cell infiltration, and bile acid metabolism. These molecular subtypes are found in 582 Asian, but less so in 265 Caucasian patients. Thus, Asian ICC and HCC, while clinically treated as separate entities, share common molecular subtypes with similar actionable drivers to improve precision therapy. Chaisaingmongkol et al. identify common molecular subtypes linked to similar prognosis in intrahepatic cholangiocarcinoma and hepatocellular carcinoma, clinically different malignancies, among Thai patients. These molecular subtypes are also found in other Asian patients, but rarely in Caucasian patients.